Pengaruh Budaya Organisasi dan Tekanan Struktural terhadap Penggunaan Diskresi Penyidik dalam Proses Penyidikan - Yasak D. SA; M Thaher; Ilham Sadikin; Rizki Ramadhan; Deshaini, Liza (Consensus : Jurnal Ilmu Hukum, 2026)
The factors that encourage investigators to exercise discretion during criminal investigations are closely linked to the practical dynamics of law enforcement, where investigators frequently encounter situations that are not explicitly regulated in detail by statutory provisions. This study aims to identify and analyze the determinants influencing investigators’ use of discretionary authority in the investigation process. The research employs a normative legal method with statutory and conceptual approaches, treating legal rules as a coherent normative system to assess the legal basis, scope, and limits of investigative discretion. The findings indicate that the use of discretion is shaped by several key factors: regulatory limitations, considerations of substantive justice, the need for efficiency in law enforcement processes, public interest considerations, social and political pressures, and the level of investigators’ professionalism and ethical standards. These findings suggest that discretion functions as an essential instrument for bridging procedural requirements and practical investigative needs in pursuit of justice, yet it must remain subject to accountability and control mechanisms to prevent misuse of authority